Evaluation of Alere i Influenza A&B for Rapid Detection of Influenza Viruses A and B - Nie, Shuping; Roth, Richard B.; Stiles, Jeffrey; Mikhlina, Albina; Lu, Xuedong; Tang, Yi-Wei; Babady, N. Esther (Journal of clinical microbiology, 2014)
Rapid and accurate diagnosis of influenza is important for infection control, as well as for patient management. Alere i Influenza A&B is an isothermal nucleic acid amplification-based integrated system for detection and differentiation of influenza virus A and influenza virus B. The performance of the Alere i Influenza A&B was screened using frozen nasopharyngeal-swab specimens collected in viral transport medium (VTM) that were originally tested fresh with the FilmArray Respiratory Panel (RP) assay during the 2012–2013 influenza outbreak. In total, 360 VTM specimens were selected for Alere i Influenza A&B testing: 40 influenza virus A H1N1-2009 (influenza virus A-1), 40 influenza virus A H3N2 (influenza virus A-3), 37 influenza virus A “equivocal” or “no subtype detected” (influenza virus A-u), 41 influenza virus B, and 202 influenza virus-negative specimens, as initially determined by the FilmArray RP assay. The Alere assay showed sensitivities of 87.2%, 92.5%, 25.0%, and 97.4% for influenza virus A-1, influenza virus A-3, influenza virus A-u, and influenza virus B, respectively, after discordant resolution by Prodesse ProFLU+ PCR. The specificities were 100% for both influenza virus A and influenza virus B. In general, the Alere i Influenza A&B provided good sensitivity, although the assay did show poorer sensitivity with samples determined to have low influenza virus A titers by Prodesse ProFlu+ PCR (a mean real-time PCR threshold cycle [C T ] value of 31.9 ± 2.0), which included the majority of the samples called influenza virus A “equivocal” or “no subtype detected” by a single BioFire FilmArray RP test. The integrated, rapid, and simple characteristics of the Alere i Influenza A&B assay make it a potential candidate for point-of-care testing, with a test turnaround time of less than 15 min.